(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This essay examines the narration style in Henry James’ novella, The Aspern Papers, by examining the varied linguistic structures that dominate the narrative. It attempts to reveal some of the stylistic choices that intensify and dramatize the retelling of the story by the unnamed narrator. This study adopts quantitative and qualitative approaches in gathering and analyzing the examined linguistic and literary content. The essay finds that in The Aspern Papers, the notorious narrator receives the sympathy of the reader instead of his two female victims, Tina and Juliana. The study highlights that the narrator manipulates language structures by choosing certain linguistic constructions in the story bringing the reader into the narrator’s disposition instead of sympathizing with his victims.